Web and mobile based GPS trail visualizer - Mayong, Andreas Chrisna (2018)
Currently, fitness has been one of the main focus in the web and mobile application development. Among those applications, tracking running activity has been one of the standard features to be implemented. This is evident by the massive amount of running tracking applications that currently exist on the market. Usually, these applications have both web and mobile version, as well as smartwatch integrations (or any other GPS-enabled devices). It works by starting a session on the application and records all the environment data provided by various sensors on the device and the GPS data for the device. At the end of the session, all the information would be compiled, summarized, and presented to the user. The user could view, edit (to some extent), and share the running activity on various social medias. GPS Trail Visualizer is a web application initially developed to add another layer of interactivity to those fitness applications. It done so by generating a 360 view of a running trail in the form of hyperlapse video using a JavaScript library called Hyperlapse.js. The images are obtained from Google Street View. This project aims to further enhance GPS Trail Visualizer by developing its mobile counterpart, as well as improve its web application. The enhancement focuses on providing better user experience, making the application more versatile, and adding more social features in it. The main features implemented in the system are “Running” mode, API server, and “View” mode. “Running” mode allows user to record their running activity using GPS Trail Visualizer mobile application. API server connects GPS Trail Visualizer to the application database. The database stores additional user data, as well as running session recorded by “Running” mode. When activated, “View” mode displays the position and username of currently online user on the map in GPS Trail Visualizer web application.